?SYNTHESIS OF 3-METHOXY-4'-PRENY- LOXY-FURANO (2'', 3'':7, 8) FLAVONE: ?Short Communication - Hossain, M Amzad; Salehuddin, S M (Biological Sciences - PJSIR, 2003)
Flavonoids represent a group of phytochemicals exhibiting a wide range of biological activities such as anti-bacterial, anti- fungal, anti-inflammatory, antimicrobial, anti-cancer and in- sect antifeedant(Hodek et al 2002). A large number of natural products including flavonoids are being reported in the lite- rature every year and their structures need to be confirmed by synthesis. In this paper, the synthesis of 3-methoxy-4'- prenyloxy-furano (2'',3'' :7,8) flavone (8) has been described starting from ?-resacetophenone (Clarke 1955) (1), which may be used as synthetic markers. ?-Resacetophenone(Clark 1955) (1) when refluxed with allyl bromide in presence of K2CO3 and acetone yielded 4-O-allylresacetophenone (Rangaswaqmi et al 1954) (2) which on Claisen migration gave 3-C-allyl-